Non-territorial Macaques Can Range Like Territorial Gibbons When Partially Provisioned With Food - Juan Manuel José-Domínguez (2018)
© 2015 Association for Tropical Biology and Conservation Inc. Human food supplementation can affect components of animal socioecology by altering the abundance and distribution of available food. We studied the effect of food supplementation by comparing the ranging patterns and intergroup interactions of two groups of northern pigtailed macaques (Macaca leonina), a non-territorial primate species. One group was partially reliant on food provisioning, whereas the other group foraged wild food. We also compared the macaques' movement with that of a group of white-handed gibbons (Hylobates lar), a territorial species inhabiting the same site. Home range, core area, and daily path lengths were significantly smaller for the semi-provisioned group than for the wild-feeding group. In contrast to wild-feeding macaques, supplemented macaques showed higher fidelity to home range, core area, and particularly to the region where human food was most accessible and abundant. The relationship of daily path length and home range indicated a low defendability index for wild-feeding macaques; the higher index for the semi-provisioned group was consistent with the territorial pattern found in gibbons. Semi-provisioned macaques showed further traits of territoriality with aggression during intergroup encounters. These findings indicate that human modification of food availability can significantly affect movement patterns and intergroup competition in macaques. The observed ranging dynamics related to food provisioning may decrease the efficiency of macaques as seed dispersers and increase predation on their home range, and thus have important consequences for plant regeneration and animal diversity.